Readership of Tebtebba Print Publications on indigenous peoples - Deliu, Teresita Pang-ot (Saint Louis College : [s.n.], 2019)
The study assessed and analyzed the readership of Tebtebba's print publications on indigenous peoples among academic libraries in Baguio City and La Trinidad, Benguet. Specifically, the study looked into the profile of Tebtebba print publications in the academic libraries according to collections, library sections, and users; the demographic profile of the users according to their profession/ field of specialization, religious affiliation, age, ethnicity, and sex, as well as the factors that affect readership of Tebtebba's print publications. This study used the case study design and phenomenological approach. Documentary analysis, questionnaire, and interview guide were the data gathering instruments. Thematic analysis with the help of using a repertory grid was used to analyze the data gathered. The study was conducted in all academic libraries in Baguio City and La Trinidad, Benguet. The respondents of the study were the 34 librarians and 134 library users who read Tebtebba's print publications. The study revealed that the Tebtebba print publications were distributed, organized in Filipiniana sections in the academic libraries, and read by students, faculty, and researchers. The users were mostly young female readers from various fields of specialization, religious affiliations, and ethnic groups. Substance, purposive requirement, and limitation are the main factors that affect the readership of TPP. The findings served as basis in crafting an action plan to further increase its readership.
References: pages 62-67.
CHED-La Union
Keywords: Academic libraries